Simulacra of Pity and The Death of Epistemic Authority: A Literature Review of The Philosophical Islamic Communication Regarding The Hyperreality of Preaching In The Post-Truth Era - Ikhwansyah Nasution; Hasan Sazali; Muhammad Randicha Hamandia; Zhila Jannati (Indonesian Journal Publisher, 2026)
This study examines how digital hyperreality and post-truth culture reshape Islamic communication and broadcasting in contemporary cyberspace. It argues that digital da’wah is no longer only a shift from physical pulpits to online platforms, but a structural transformation of religious meaning, authority, and public reasoning. Using a qualitative library-based design, the research analyzes recent scholarly works on digital da’wah, religious influencers, epistemic authority, Islamic communication ethics, platform governance, and communication regulation. The study applies qualitative content analysis and critical discourse interpretation to identify how algorithmic visibility, audience engagement, symbolic performance, and misinformation influence Islamic messages in digital public spaces. The findings show that digital da’wah may expand access to religious knowledge, yet it also risks commodifying piety, weakening scholarly authority, and reducing complex Islamic teachings into emotional and fragmented content. To address this crisis, Islamic communication philosophy offers ethical principles such as qaulan sadida, qaulan baligha, tabayyun, and amanah as foundations for truthful and responsible communication. The study proposes that future Islamic communication policy must combine digital literacy, epistemic accountability, algorithmic transparency, and ethical co-regulation to protect truth, dignity, public trust, and religious authority in the post-truth era. It strengthens Islamic broadcasting studies by linking ethics, regulation, and platform accountability.